2020
DOI: 10.1002/cnma.201900690
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Mechanisms of All‐Inorganic Cesium Lead Bromide Perovskites Revealed by Single Particle Spectroscopy

Abstract: Metal halide perovskites (MHPs) are promising materials for a range of optoelectronic applications owing to their unique structures and optical properties. The photoluminescence (PL) property of MHPs is crucial for their applications. All‐inorganic MHPs such as CsPbBr3, CsPb2Br5 and Cs4PbBr6, have been widely investigated due to their high PL quantum yield (QY). However, the PL mechanisms of these perovskites still remain controversial and lack a unifying explanation. In this review, we have summarized the rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…This is very similar to the case of the size‐independent emission observed in Cs 4 PbBr 6 . Although the detailed origin of the emission is still under debate, over the past years of research, it is concluded that the origin of the “CsPbBr 3 ‐like” emission in Cs 4 PbBr 6 is either from trace amount of CsPbBr 3 phase or the structural defect of Cs 4 PbBr 6 [51,52] . In our case, the shift of the UV‐vis is also related to the occurrence of Cs 4 PbCl 6 , although whether it is from trapped CsPbCl 3 or structural defect still requires further investigation.…”
Section: Resultsmentioning
confidence: 64%
“…This is very similar to the case of the size‐independent emission observed in Cs 4 PbBr 6 . Although the detailed origin of the emission is still under debate, over the past years of research, it is concluded that the origin of the “CsPbBr 3 ‐like” emission in Cs 4 PbBr 6 is either from trace amount of CsPbBr 3 phase or the structural defect of Cs 4 PbBr 6 [51,52] . In our case, the shift of the UV‐vis is also related to the occurrence of Cs 4 PbCl 6 , although whether it is from trapped CsPbCl 3 or structural defect still requires further investigation.…”
Section: Resultsmentioning
confidence: 64%
“…As reported in previous studies, 4,12,26 among all the lead halide perovskite nanoparticles, the bromide perovskite (CsPbBr 3 ) QDs have the most promising properties. The absorption band has been associated with the Pb 2+ (6s)− Pb 2+ (6p) transition.…”
mentioning
confidence: 68%
“…39 One possible explanation of the longer coherence time observed for these perovskite QDs could be due to the presence of allowed dipole moment triplet states in the conduction band. 26,34,40,81,82,88 These states, in fact, present a smaller energy gap fluctuation which can help to preserve the coherent superposition state for longer times.…”
mentioning
confidence: 99%
“…[ 33,34 ] Owing to the nanoscale physical size of CsPbBr 3 NPs, the quantum confinement of charge carriers occurs. [ 35 ] Spatial constraint prevents electron and hole separation and induces recombination, resulting in a high PL. In bulk CsPbBr 3 , quantum confinement does not occur, and electrons and holes are easily separated and/or trapped on the surface or in defects, leading to nonradiative recombination and low PL.…”
Section: Resultsmentioning
confidence: 99%